Effects of collisions on the generation and suppression of temperature anisotropies and the Weibel instability - K. M. Schoeffler; L. O. Silva (Physical Review Research, 2020)
The expansion of plasma with nonparallel temperature and density gradients and the generation of a magnetic field via the Biermann battery is modeled using particle-in-cell simulations that include collisional effects via Monte Carlo methods. A scaling of the degree of collisionality shows that an anisotropy can be produced and drive the Weibel instability for gradient scales shorter than the mean free path. For larger collision rates the Biermann battery dominates as the cause of magnetic-field generation. When the most energetic particles remain collisionless the Nernst effect causes the Biermann field to be dragged with the heat flux piled up and enhanced.